2022
DOI: 10.1111/ibi.13045
|View full text |Cite
|
Sign up to set email alerts
|

Predicting population trends of birds worldwide with big data and machine learning

Abstract: Birds are crucial for the functioning of Earth’s ecosystems but bird population declines have been documented worldwide in recent decades. A global assessment of potential causes of population declines is needed. Our goal here was to combine the power of big data and machine learning to identify predictors correlated with bird population declines and to predict population declines for species with unknown population trends on the IUCN Red List. From existing online databases, we gathered detailed species‐level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated proof-of-concept for predictive modelling approaches for monitoring or conservation prioritization for plant and animal groups, but at continental or global scales (Bastin et al, 2019; Parsons, Pelletier, Wieringa, Duckett, & Carstens, 2022; Pelletier et al, 2018; Wieringa, 2022; Zhang, Campomizzi, & Lebrun-Southcott, 2022; Zizka et al, 2022). Because decisions about monitoring, research, and protection are often made at smaller spatial scales, before recommending adoption of these tools for conservation practice, it is crucial to determine if they still provide useful predictions at those scales (Meyer & Pebesma, 2021; Wyborn & Evans, 2021), as we have done here.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated proof-of-concept for predictive modelling approaches for monitoring or conservation prioritization for plant and animal groups, but at continental or global scales (Bastin et al, 2019; Parsons, Pelletier, Wieringa, Duckett, & Carstens, 2022; Pelletier et al, 2018; Wieringa, 2022; Zhang, Campomizzi, & Lebrun-Southcott, 2022; Zizka et al, 2022). Because decisions about monitoring, research, and protection are often made at smaller spatial scales, before recommending adoption of these tools for conservation practice, it is crucial to determine if they still provide useful predictions at those scales (Meyer & Pebesma, 2021; Wyborn & Evans, 2021), as we have done here.…”
Section: Discussionmentioning
confidence: 99%
“…The steepest declines were observed in forest-specialized invertivores, a group known to be particularly sensitive to the effects of deforestation and fragmentation ( 14 , 29 ), and matching findings from other Neotropical forests ( 14 , 28 ). A recent global analysis of avian population declines found that severe population fragmentation was the best predictor for declines in nonmigratory birds in South America ( 30 ). In this system, for example, the Rufous Mourner ( Rhytipterna holerythra ) and the Northern Nightingale-wren ( Microcerculus philomela ) are sensitive to habitat fragmentation, effects that have driven local extirpations throughout Costa Rica ( 15 , 31 ); these same species were characterized by rapidly declining population sizes in this study.…”
Section: Discussionmentioning
confidence: 99%